2016
DOI: 10.1007/s12576-016-0465-0
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of resveratrol on angiotensin II levels and the rate of transcription of its receptors in the rat cardiac hypertrophy model

Abstract: This study investigated the effect of resveratrol on serum and cardiac levels of angiotensin II and transcription of its main receptors following pressure overload induced-hypertrophy. Rats were divided into untreated (Hyp) and resveratrol treated hypertrophied groups (H + R). Intact animals served as the control (Ctl). Cardiac hypertrophy was induced by abdominal aortic banding. Blood pressure (BP) was recorded via left carotid artery cannula. Fibrosis was confirmed by Masson trichrome staining. Angiotensin I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Some investigations have also shown the anti-hypertrophic effects of resveratrol. For example, in our previous study, we reported that following hypertrophy induced by abdominal aortic banding in rat, resveratrol exerts antihypertrophic effects at a non-hypotensive dose, in part by normalizing AT1a mRNA levels (Mashhadi et al, 2017). Resveratrol exerts its antihypertrophic effect by decreasing protein synthesis and cellular growth due to phenylephrine in rat cardiac myocytes (Chan et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Some investigations have also shown the anti-hypertrophic effects of resveratrol. For example, in our previous study, we reported that following hypertrophy induced by abdominal aortic banding in rat, resveratrol exerts antihypertrophic effects at a non-hypotensive dose, in part by normalizing AT1a mRNA levels (Mashhadi et al, 2017). Resveratrol exerts its antihypertrophic effect by decreasing protein synthesis and cellular growth due to phenylephrine in rat cardiac myocytes (Chan et al, 2008).…”
Section: Discussionmentioning
confidence: 96%
“…Cardiac hypertrophy index (mg/g) was calculated from the total heart weight (mg) relative to total body weight (g) of the rat. 22…”
Section: Methodsmentioning
confidence: 99%
“…Resveratrol upregulates ACE2, increases Ang (1-7), stimulates Masreceptors, decreases Ang II levels and downregulates angiotensin-AT 1 receptor expression in the ageing kidney and also in animal models of cardiac hypertrophy (Dorri Mashhadi et al, 2017;Jang et al, 2018). Similar changes have been observed in aortic tissues of ageing animals where the drug exerted anti-inflammatory, anti-fibrotic and antioxidant actions (Kim et al, 2018).…”
Section: Resveratrolmentioning
confidence: 70%